The effect of lycopene supplement from different sources on prostate specific antigen (PSA): A systematic review and meta-analysis of randomized controlled trials☆ - Elham Sharifi-Zahabi; Sepideh Soltani; Mahsa Malekahmadi; Laya Rezavand; Cain C.T. Clark; Farzad Shidfar (Elsevier, 2022)
Background: Prostate cancer is a major malignancy, affecting men, worldwide. The protective effect of dietary or supplemental lycopene on prostate cancer has been reported in several studies; however, the findings are equivocal. Objective: The aim of this study was to evaluate the effects of supplemental lycopene on PSA level, by conducting a systematic review and meta-analysis of randomized controlled trials. Methods: We searched online databases, including PubMed, Scopus, and Web of Science, up to 9 Jun 2020, to obtain relevant publications. The publication search was not limited by language or date. Results: A total of 1036 records were identified in the systematic search; from these, 9 were included in the systematic review and 6 in meta-analysis. The pooled analysis of the 6 studies showed no significant differences in PSA levels in subjects treated with lycopene or tomato extract containing lycopene (WMD= −0.12 ng/ml; 95% CI: −0.62, 0.38 ng/ml; P = 0.64) compared to the control. Conclusion: Overall, tomato extracts or lycopene treatment yielded no significant effect on PSA level compared to the control. However, more consistent clinical trials, with larger sample sizes, are required to better discern the actual effect of tomato extract or lycopene on PSA level.